Pseudochromadora benepapillata (Timm 1961) comb. n. (Desmodoridae: Nematoda): revision of its taxonomic status and distribution - Datta, Tridip Kumar; Ganguly, Arundhati; Chakraborty, Susanta Kumar (Zootaxa, 2018)
Metachromadora (Bradylaimoides) benepapillata, was first discovered from the coastal mangroves of Bangladesh by Timm (1961). This species was later synonymised with Pseudochromadora cazca, which was described from the Brazilian coast by Gerlach (1956). The present paper proposes to update the taxonomic status of the Timm’s species as Pseudochromadora benepapillata comb. n. along with its distribution and comparative morphology. The major differences between P. cazca and P. benepapillata are found in the characteristics of the head capsule; length of cephalic sensilla; length and position of somatic setae; shape of amphideal fovea; shape of spicules and gubernaculum; number and morphology of copulatory and postcloacal thorns. The present report on the occurrence of this species along the eastern most coast of India extends its distribution from the eastern part of Bay of Bengal to its western part.